Baligraphy Becomes an Innovative Approach to Learning Balinese Language and Culture (LACULTOUR: Journal of Language and Cultural Tourism, 2026)
ABSTRACT This study aims to analyze the role of baligraphy as an innovative approach in learning Balinese language and culture. Baligraphy is a visual art form that combines Balinese script with aesthetic elements, so it not only has artistic value, but also educational and cultural value. This study uses a descriptive qualitative approach with data collection techniques such as literature study, observation, and documentation. The results show that baligraphy can increase students' interest and motivation in learning Balinese script through creative activities involving visual and motor aspects. In addition, baligraphy helps strengthen students' understanding of the structure of Balinese script through the process of repetition in creative practice. Baligraphy also plays a role in fostering creativity and is an effective medium in conveying Balinese philosophical and cultural values ??to the younger generation. In an educational context, baligraphy is relevant to be applied in project-based learning in accordance with the principles of the Independent Curriculum, because it encourages contextual, active, and experience-based learning. Thus, baligraphy can be an innovative strategy that integrates aspects of language, art, and culture while supporting the preservation of Balinese culture in the era of globalization.